A natural mutation of the NST1 gene arrests secondary cell wall biosynthesis in the seed coat of a hull-less pumpkin accession. Issue 1 (16th June 2022) - Lyu, Xiaolong; Shi, Lu; Zhao, Meng; Li, Zhangping; Liao, Nanqiao; Meng, Yiqing; Ma, Yuyuan; Zhou, Yulan; Xue, Qin; Hu, Zhongyuan; Yang, Jinghua; Zhang, Mingfang
Abstract: Hull-less pumpkins ( Cucurbita pepo L.) are naturally occurring novel variants known as oilseed or naked-seeded pumpkins, and are characterized by the absence of a normal lignified seed coat. Due to a specialized seed coat structure, these variants serve as a good model for studying seed coat formation and simplify the processing of pumpkin seeds. However, causal genes for this hull-less trait still remain unknown. Here, by Bulked Segregant Analysis (BSA) and fine mapping, we found that mutation of a single gene, NAC SECONDARY WALL THICKENING PROMOTING FACTOR 1 ( NST1 ), accounts for the hull-less trait. A 14-bp sequence insertion in the CpNST1 gene causes premature termination of CpNST1 translation, leading to lack of secondary cell wall (SCW) biosynthesis in hull-less seed coats. In situ hybridization analysis provided further evidence for the role of CpNST1 in pumpkin seed coat SCW biosynthesis. Interestingly, through secondary cell wall compositional analysis, we found that the main SCW components differed among cell layers in the seed coat. RNA-seq analysis indicated an upstream role of CpNST1 in the SCW biosynthesis network. Collectively, our findings provide mechanistic insight into seed coat SCW biosynthesis, and a target gene as well for breeders to introduce this hull-less trait for commercial exploitation.